(untitled) (Marketing Journal, 2026)
Abstract This study examines the long-run and short-run effects of strategic governance quality and research capacity on the competitiveness of higher education in Uzbekistan. Using annual time-series data for the period 2000-2022, higher education competitiveness is proxied by tertiary school enrollment, while institutional quality and scientific capacity are captured by government effectiveness, regulatory quality, scientific and technical journal articles, and the number of researchers in R&D. Given the mixed order of integration and small sample size, the Autoregressive Distributed Lag (ARDL) bounds testing approach is employed to investigate cointegration and dynamic relationships among the variables. The results provide evidence of a stable long-run equilibrium relationship between higher education enrollment, governance quality, and research capacity. Scientific publication output and the stock of R&D researchers are found to be key long-run drivers of tertiary education expansion, while institutional quality indicators influence higher education development through delayed and dynamic adjustment processes. The error-correction term confirms a significant speed of adjustment toward long-run equilibrium, indicating that deviations from the steady-state path are corrected over time. These findings highlight the crucial role of strategic governance reforms and sustained investment in research and innovation infrastructure in building sustainable competitive advantage in the higher education sector of transition economies. Keywords: higher education competitiveness, governance quality, research capacity, ARDL model, cointegration, institutional quality, R&D, Uzbekistan.